2007
DOI: 10.1200/jco.2007.25.18_suppl.1522
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life among high-risk women in an MRI surveillance study

Abstract: 1522 Background: The quality of life (QOL) and psychological impact of incorporating MRI into breast cancer screening programs for high-risk women (HRW) has not been well studied. Psychological and biological risk factors, e.g. cancer history, BRCA mutation, imaging recall, generalized anxiety or clinical depression may mediate QOL outcomes. Methods: 100 HRW undergoing intensive surveillance including yearly mammography, semiannual breast ultrasound and breast MRI have completed QOL (SF-36), anxiety (STAI) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Stress and anxiety appear most often among those actively undergoing genetic testing or counseling ( Moyer, 2014 ) and afterward due to prophylactic treatment since their stress has been found to be highest due to test results and surgeries for subsequent risk reduction ( Wenzel et al, 2012 ). BRCA1/2 -positive women who have received clear surveillance results (no abnormalities seen), for instance, concurrently have reported better HRQoL scores ( Bradbury et al, 2007 ). As shown in previous literature by Metcalfe and colleagues ( Metcalfe et al, 2015 ), HRQoL appears to be fluid over time, relative to when choices are made regarding these treatments and if any cancer diagnosis occur.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stress and anxiety appear most often among those actively undergoing genetic testing or counseling ( Moyer, 2014 ) and afterward due to prophylactic treatment since their stress has been found to be highest due to test results and surgeries for subsequent risk reduction ( Wenzel et al, 2012 ). BRCA1/2 -positive women who have received clear surveillance results (no abnormalities seen), for instance, concurrently have reported better HRQoL scores ( Bradbury et al, 2007 ). As shown in previous literature by Metcalfe and colleagues ( Metcalfe et al, 2015 ), HRQoL appears to be fluid over time, relative to when choices are made regarding these treatments and if any cancer diagnosis occur.…”
Section: Introductionmentioning
confidence: 99%
“…Although genetic testing/counseling provides preventive opportunities for risk management, it has been shown to decrease HRQoL in response to increases in anxiety/stress as well as the life-changing nature of what a positive genetic test means for not only the individual but the family unit ( Harmsen et al, 2015 ). Research has demonstrated the importance of understanding HRQoL among BRCA1/2 -positive individuals regarding prophylactic (preventive) decision-making and ongoing surveillance despite increased in-person provider communication and knowledge ( Connors et al, 2014 , Dean, 2016 ) and adverse psychosocial reactions to these genetic testing/counseling and results, surgeries, and surveillance measures ( Bradbury et al, 2007 , Jones et al, 2020 ). Previous research, however, does not examine potential differences among subpopulations of BRCA1/2 -positive samples, such as those with cancer recurrence(s) or those without cancer, due to relatively small sample sizes that have most notably qualitative decision-making and family interactions thus limiting implications assisting medical professionals working directly with these populations ( Donnelly et al, 2013 , Rowland et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%